Erythrogram, leukogram, and acute phase protein reference intervals for healthy newborn Murrah buffalo calves (Bubalus bubalis) within the first month of life - Santana, André Marcos [UNESP]; da Silva, Daniela Gomes [UNESP]; Clemente, Virna [UNESP]; Bernardes, Priscila Arrigucci [UNESP]; Pizauro, Lucas José Luduverio [UNESP]; Santana, Clarissa Helena [UNESP]; Thomas, Funmilola Clara; McCulloch, Eilidh; Eckersall, Peter David; Fagliari, José Jurandir [UNESP] (Springer Nature, 2017)
Establishing of reference intervals (RI) for hematologic variables and blood serum acute phase proteins (APP) of healthy newborn buffaloes is an important tool for monitoring alterations during infection and inflammation. Considering the scarcity of published data on newborns, the aim of the study was to establish RI for hematologic variables and APP from healthy newborn buffaloes. Blood samples from 28 healthy Murrah buffalo calves, 10–30 days old, were selected to determine RI. Fourteen hematologic and four blood APP variables were analyzed. Before collection of blood samples, calves were subjected to physical examination (rectal temperature, degree of dehydration, and fecal consistency) and only calves that were considered healthy were included in the study. The Anderson-Darling test was used to assess normal distribution of values. The Dixon test and Tukey test were used to identify outliers. RI and 90% CI were determined using standard/robust methods and Box-Cox transformation. RI for variables analyzed were the following: (1) hematologic variables: RBC 7.5–12.9 × 106/μL, HGB 10.6–19.0 g/dL, packed cell volume 33.1–54.8%, mean corpuscular volume 36.2–50.6 fL, mean corpuscular hemoglobin 12.1–17.3 pg, mean corpuscular hemoglobin concentration 28.1–42.9 g/dL, platelets 361–1081 × 103/μL, WBC 6.56–18.2 × 103/μL, lymphocytes 4.15–12.8 × 103/μL, segmented neutrophils 0.950–10.6 × 103/μL, band neutrophils 0–0.160 × 103/μL, monocytes 0–0.754 × 103/μL, eosinophils 0–0.326 × 103/μL, and basophils 0–0.149 × 103/μL and (2) APP variables: fibrinogen 2.49-9.50 g/L, haptoglobin 0.02-0.56 g/L, serum amyloid A (SAA) 3.70-97.51 μg/mL, and C-reactive protein (CRP) 0.02-2.78 μg/mL. In conclusion, hematologic and acute phase protein RI have been documented and can be used as a physiologic database to help the interpretation of laboratory results of newborn buffaloes during infection and inflammation conditions.
Keywords: Haptoglobin; Hematology; Infection; Inflammation; Neonatal